2019
DOI: 10.1080/17518423.2019.1687602
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Repeat AbobotulinumtoxinA (Dysport®) Injections in Improving Gait in Children with Spastic Cerebral Palsy

Abstract: Purpose: This secondary analysis of a randomized, double-blind study plus open-label extension (NCT01249417/NCT01251380) evaluated the efficacy of abobotulinumtoxinA versus placebo in improving gait pattern in children with dynamic equinus due to cerebral palsy (CP) as assessed by the observational gait scale (OGS). Methods: Ambulatory children with CP (N = 241, aged 2-17) and dynamic equinus were randomized to treatment with abobotulinumtoxinA (10 or 15U/kg/leg) or placebo injected into the gastrocsoleus. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Functional efficacy of BoNT-A on treatment goals and gait function of ambulatory children with CP presenting with equinus foot deformity were revealed by repeat aboBoNT-A injections to relevant lower limb muscles in a large international trial by the Goal Attainment Scale (GAS) and Observational Gait Scale (OGS). 24 25 Sahoo et al reported that children with CP having GMFCS levels of III to V had lower scores in CASP questionnaire in all areas of participation to daily life compared with children with GMFCS levels I and II. 26 Aiming to show the impact of improvement in muscle tone and spasticity on activity, and participation domains of ICF, CPCHILD, and CASP questionnaires were used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Functional efficacy of BoNT-A on treatment goals and gait function of ambulatory children with CP presenting with equinus foot deformity were revealed by repeat aboBoNT-A injections to relevant lower limb muscles in a large international trial by the Goal Attainment Scale (GAS) and Observational Gait Scale (OGS). 24 25 Sahoo et al reported that children with CP having GMFCS levels of III to V had lower scores in CASP questionnaire in all areas of participation to daily life compared with children with GMFCS levels I and II. 26 Aiming to show the impact of improvement in muscle tone and spasticity on activity, and participation domains of ICF, CPCHILD, and CASP questionnaires were used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly higher decreases of muscle hypertonia and spasticity (MAS, MTS), goal achievement (GAS), and overall global clinical impression (PGA) were demonstrated for the treatment groups [22,40,41]. In the double-blind phase, AboBoNT-A significantly improved observational gait scale (OGS) total scores versus placebo at week 4, and continued to improve gait throughout the OL phase [42]. Importantly, a long-term therapeutic effect was demonstrated: 74% of children treated did not require retreatment before week 16 or later, with 17.7% of patients not requiring retreatment before week 28 [40].…”
Section: E a D I N G T O P I Cmentioning
confidence: 99%
“…Strikingly, in most of the previous studies only the BoNT-A part was put forward as the effective component, thus disregarding the (potential) contribution of the modalities from the comprehensive rehabilitation part, such as physiotherapy, casting and orthosis (e.g. (5,6,(20)(21)(22)(23)(24) (Fig. 1b).…”
Section: Interpretation and Presentation Of Previous Researchmentioning
confidence: 99%